Healthcare Awareness Improves Infant Health: A Case Study of Bahawalpur, Punjab, Pakistan - Hureem, Uzooba; Davis, Dr. G. Douglas (International Journal of Social and Management Studies, 2024)
The infant mortality rate is considered a key indicator of the state of a community’s public health and social development. Developing countries, especially Pakistan, have the highest infant mortality rate. This case study highlights the impact of healthcare awareness programs on reducing the infant mortality rate in Bahawalpur, Pakistan. The in-depth analysis indicates that healthcare awareness programs change the care-seeking behavior and attitude of the local people toward professional maternal and newborn healthcare. Moreover, knowledge of newborn care, skilled birth attendance, and danger signs of illness among rural communities contributes to decreasing the infant mortality rate in Bahawalpur, Pakistan.